2x − 2y + 10z = 6 4x − 2y + 16z = 7 3x −

2x − 2y + 10z = 6 4x − 2y + 16z = 7 3x − 2y + 14z = −4
Show more >

Answer:

  • ** - ** * *** * * **
    **
    - 2y * *** * 7 ** (2)
    -
    *** ****** ** +
    6z
    * * 3 3x - **
    *
    *** * ** ** *** * *** gives
    *
    * 2z = **
    **
    * * (5) ****** ** +
    **
    = ** ** ***
    *
    *** ****** ** * *** so
    *
    * -21/2 ******* *
    *****
    in (5) ** **** * + *
    *
    (-21/2) *...

    $10.00

    Buy an answer

Learn more effectively and get better grades!

Do my homework